Posttraumatic Isolated Diffuse SAH Because of Atlas (C1) Fracture Involving Transverse Process without Vertebral Artery Injury: A Case Report - Akshay Patil; Sandip Iratwar; Ashish Jha (Indian Journal of Neurosurgery)
Traumatic subarachnoid hemorrhage (SAH) can be seen in mild, moderate, and severe head injury. Traumatic SAH is usually present in the sulci or superficial subarachnoid space (SAS) of the cortex rather than in the basal SAS. Basal SAH is usually harmful because of the injury to vascular structure resulting into vasospasm and ischemia. Here we are presenting a rare case in which patient is presented with traumatic injury to the neck followed by the isolated diffuse SAH mostly basal without injury to the brain parenchyma. Patient was presented with the raised intracranial pressure features (headache, vomiting) and seizure. On admission, he had a Glasgow Coma Scale of E3V3M5. His computed tomography (CT) of the brain was suggestive of diffuse SAH in all cisterns especially in basal cistern. He was evaluated by angiogram that was suggestive of no major vascular involvement. His CT cervical spine was suggestive of Atlas (C1) fracture involving transverse process with medial and inward displacement of bone, probably causing vascular insult in the form of venous injury leading to the SAH.